Effect of water deficit on growth and fruit quality of autumn-winter pepper - HAN Jinzhao; FENG Junjie; ZHAI Guoliang; XU Honggang; WANG Ming; SONG Lei; HAO Pingping (Guan'gai paishui xuebao, 2024)
【Background and Objective】 Pepper is a shallow-rooted cash crop characterized by high leaf area index (LAI) and stomatal conductivity. It is sensitive to soil water change, and excessive or insufficient irrigation could thus inhibit its development, resulting in a decrease in yield and fruit quality. Reducing irrigation amount at different growth stages to maintain soil moisture at optimal levels has been posited as an improved cultivation method to improve yield and quality of the pepper. This paper aims to investigate the effect of water deficit at different growth stages on growth, yield and quality of chili pepper in the middle and low reaches of the Yellow River. 【Method】 The experiment was conducted in a solar greenhouse in Xinxiang, Henan province, with the pepper irrigated by drip irrigation. Three water deficits were imposed at flowering-fruiting stage (K) and fruiting stage (J) at different levels: severe water deficit by keeping the soil moisture content at 55%-65% of the field capacity (K1 and J1), moderate water deficit by keeping soil moisture content at 65%-75% of the field capacity (K2 and J2), sufficient irrigation by keeping soil moisture content at 75%-85% of the field capacity (K3 and J3). In each treatment, we measured plant height, stem diameter, yield and fruit quality of the pepper. 【Result】 ① Water deficit in reproductive stage reduced plant height and stem diameter of the pepper, while a moderate water deficit in flowering-fruiting stage and fruiting stage did not significantly affect plant height and stem diameter. ② The combination of K2 and J3 increased the yield of the pepper, promoted formation of marketable fruits. Compared with the combination of K3 and J3, the combination K2+J3 increased the yield of marketable fruits by 18.9%. ③ The combination of K2 and J3 had the highest soluble sugar content; the combination of K1 and J1 gave the highest dihydrocapsaicin content; the combination of K2 and J2 had the highest capsaicin, soluble protein, and vitamin C content. 【Conclusion】 A moderate water deficit during the flowering - fruiting stage combined with a sufficient irrigation at fruiting stage can improve yield and fruit quality for the greenhouse chili pepper.